Konsep Pengaturan Hewan Peliharaan sebagai Objek Jaminan dalam Hukum Indonesia - Anadi, Yandri Radhi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article explores the urgency and conceptual framework for regulating pets as collateral objects within Indonesia’s legal system to establish legal certainty that aligns with animal welfare principles. Under the civil law framework, animals are still classified as movable objects without adequate legal protection for their fundamental rights as living beings. This situation creates a legal vacuum that leads to ethical, social, and legal issues in the practice of collateral. The issues examined include the legal status of pets as collateral in Indonesia, as well as the ideal regulatory concept and model that can ensure a balance between economic value and the protection of animals' fundamental rights. This research employs a normative juridical method with a statutory approach and a comparative study of the legal systems of Turkey and Australia. The findings show that although, in theory, pets can be used as collateral due to their classification as movable property, the absence of regulation gives rise to legal, ethical, and uncertainty-related issues. Comparisons with other countries emphasize the need for an ideal regulatory model that balances economic value with the protection of animals’ fundamental rights through clear legal definitions, independent valuation, mandatory care, and humane execution procedures. Thus, this article makes a vital contribution to the development of a more just and sustainable collateral law while also strengthening Indonesia’s position in responding to international legal developments concerning animal protection.